Ab initio models for six-center multiple proton exchange and ion pair formation assisted by Lewis acids - van Eikema Hommes, Nico; Heidrich, Dietmar; Schleyer, Paul (Journal of Molecular Modeling, 2000)
High level ab initio and density functional calculations, extrapolated to QCISD(T)/6-311+ G(3df,2p)//MP2/6-31+G**+ZPE, reveal that cyclic ion pairs can form in the hydrogen bonded complexes of haloboric acids BHnX3-n-HX, X=F, Cl, with Lewis bases HX, H2O, CH3OH, and NH3, even in isolation (e.g., in the gas phase). The intrinsic acidities (deprotonation energies) required for protonation of these bases with formation of gas phase ion pairs are calculated to be <295 kcal/mol for water, <301 kcal/mol for methanol, and <306 kcal/mol for ammonia; such values are common for acidic sites in zeolites. All gas phase ion pairs prefer symmetric bidentate or tridentate structures. In the other cases where hydrogen bonded complexes prevail, symmetric ion pair-like transition structures for multiple hydrogen exchange are computed.
Keywords: gas phase ion pairs; multiple proton exchange; ab initio calculations; density functional calculations